2016
DOI: 10.1136/bmjopen-2016-011363
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and medium-term survival of critically ill patients with solid tumours admitted to the intensive care unit: a retrospective analysis

Abstract: ObjectivesPatients with cancer frequently require unplanned admission to the intensive care unit (ICU). Our objectives were to assess hospital and 180-day mortality in patients with a non-haematological malignancy and unplanned ICU admission and to identify which factors present on admission were the best predictors of mortality.DesignRetrospective review of all patients with a diagnosis of solid tumours following unplanned admission to the ICU between 1 August 2008 and 31 July 2012.SettingSingle centre tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 51 publications
5
23
0
Order By: Relevance
“…Similar to our study, severity of illness (measured by the SOFA score) has been described in literature as predictor for short-term mortality in patients with a malignancy (30,31,41) and long-term mortality (38,39,42). Studies which describe SOFA score and performance status as long-term predictor have maximal 1 year of follow up after ICU admission.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to our study, severity of illness (measured by the SOFA score) has been described in literature as predictor for short-term mortality in patients with a malignancy (30,31,41) and long-term mortality (38,39,42). Studies which describe SOFA score and performance status as long-term predictor have maximal 1 year of follow up after ICU admission.…”
Section: Discussionsupporting
confidence: 85%
“…invasive mechanical ventilation) [19,20], and comprises two cancer-specific variables (e.g. clinical stage of cancer and non-malignancy-related admission) related with mortality in cancer patients admitted to ICU [10,21]. Thus, it is not surprising a better fitting and discrimination with APACHE-II CCP model than those observed with general predictive models.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of critically ill cancer patients admitted to the ICU have revealed that age alone was not a predictor of mortality (10)(11)(12)(13)(14). Severity of clinical condition as assessed by SAPS 2, Sequential Organ Failure Assessment (SOFA), Acute Physiology, Chronic Health Evaluation II (APACHE) or similar methods at ICU admission was of utmost importance rather than age.…”
mentioning
confidence: 99%
“…Severity of clinical condition as assessed by SAPS 2, Sequential Organ Failure Assessment (SOFA), Acute Physiology, Chronic Health Evaluation II (APACHE) or similar methods at ICU admission was of utmost importance rather than age. Uncontrolled or metastatic disease (11-13), sepsis or septic shock (11,12), organ dysfunction (11,12), performance status (12,13), use of mechanical ventilation (12)(13)(14), and type of solid tumor (14) were other factors associated with hospital mortality.…”
mentioning
confidence: 99%